Rascal - North, Sterling, 1906-1974.; Schoenherr, John (New York : Scholastic, 1963)
The author recalls his carefree life in a small midwestern town at the close of World War I, and his adventures with his pet raccoon, Rascal.
Keywords: North, Sterling, -- 1906-1974 -- Biography -- Youth; Authors, American -- 20th century -- Biography; Rascal (Raccoon); Procyon -- Wisconsin -- Biography; Raccoon -- Wisconsin -- Biography; Country life -- Wisconsin; Procyon; Raccoon